Smoking and Non-Neoplastic Lung Disease in Canadian Men and Women - Mary Jane Ashley; Bernard CK Choi; Anita WP Pak (Canadian Respiratory Journal)
MAIN OBJECTIVE: To document and assess the current health impact of non-neoplastic lung disease (NNLD) in Canadian men and women that is attributable to smoking.